2019
DOI: 10.17129/botsci.2204
|View full text |Cite
|
Sign up to set email alerts
|

Seed bank formation and removal of Pinus hartwegii (Pinaceae) seeds along an altitudinal gradient in the Cofre de Perote National Park, Veracruz, Mexico

Abstract: Background: Seed banks, an important element in the natural regeneration of plant communities, are regulated mostly by granivores along an altitudinal gradient. Question/Hypothesis: Pinus hartwegii forms transient and probably persistent seed banks along an altitudinal gradient. Seed removal will vary according to the removing agents, the altitude and the season. Species under study/Data description/Mathematical model: The formation of seed banks and the removal of Pinus hartwegii (Pinaceae) seeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
0
0
1
Order By: Relevance
“…The distribution patterns of the devitalized trees found in the present study may also be related to the decline in the reproductive performance of this species with respect to an altitudinal gradient. For example, Tejeda-Landero et al [92] evaluated the viability of P. hartwegii seeds at four altitudes (3400, 3600, 3800, and 4000 m) within the Cofre de Perote National Park, Veracruz, Mexico. The main results of this study showed that the highest values of seed viability occurred at the upper limits, in contrast to those of the lower altitude site.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution patterns of the devitalized trees found in the present study may also be related to the decline in the reproductive performance of this species with respect to an altitudinal gradient. For example, Tejeda-Landero et al [92] evaluated the viability of P. hartwegii seeds at four altitudes (3400, 3600, 3800, and 4000 m) within the Cofre de Perote National Park, Veracruz, Mexico. The main results of this study showed that the highest values of seed viability occurred at the upper limits, in contrast to those of the lower altitude site.…”
Section: Discussionmentioning
confidence: 99%
“…de la vegetación arbórea en México y, muy importante, en los servicios ecosistémicos de regulación (Alfaro-Ramírez et al 2020). La especie tiene ciclos semilleros hasta de cinco años y, en las últimas décadas, su producción de semilla ha decrecido dramáticamente, lo cual se refleja en una limitada regeneración natural (Tejeda-Landero et al 2019). Algunos estudios señalan que la especie tendrá una disminución en su área de distribución de hasta el 80 %, con impacto negativo para su ecosistema (Gutiérrez y Trejo 2014).…”
Section: Introductionunclassified